The Impact of Water-Related Challenges on Rural Communities Food Security Initiatives - Ndivhoniswani Nephawe; Marizvikuru Mwale; Jethro Zuwarimwe; Malose Moses Tjale (AGRARIS: Journal of Agribusiness and Rural Development Research, 2021)
Water scarcity has been a critical concern in many countries of the world. The same concern has been discussed, analyses and researched at different platforms to find better solutions to the challenges of water scarcity, and in most cases water scarcity directly influence food security in terms of food production. South Africa, being one of the water scarce countries that derives its food from the agricultural sector; water scarcity remains at the center stage of the national socioeconomic debate. Water scarcity is one of the major challenges in many countries such as Zimbabwe and Ethiopia particularly for the farmers. However, there is insufficient information on the impact of water scarcity challenges on rural communities’ food security initiatives. This review is focused on unearthing water scarcity challenges in rural communities, their impact on agriculture and ultimately food security initiatives. This paves way for possible research areas, practical implications and strategies to mitigate water security effects on food security.